Early steps of an alternative test meal for gastric emptying scintigraphy - Şan, Hüseyin; Çalışkan, Mehmet Bahadır (Vojnosanitetski pregled, 2022)
Background/Aim. Gastric emptying (GE) scintigraphy provides a physiologic and noninvasive measurement of GE. Although GE scintigraphy has been standardized, preparing a meal is still complex and not practical in daily routine. The aim of the study was to prepare a simple, practical, and easily standardizable semisolid meal and investigate its role in estimating the GE function in of rabbits. Methods. In the first part of the study (basal condition), the mixture of the macroaggregated albumin (MAA) labeled with 37 MBq (1 mCi) of technetium-99m (99mTc) and 40 g of barium sulfate (1g/mL) was applied to animals via a nasogastric catheter. A series of images (frame/min, 60 min) in the anterior and posterior projections were dynamically acquired, and the motion was corrected after the radiopharmaceutical application. A few days later, the same rabbits were scanned under the same protocol after a 1 mg atropine injection to simulate gastroparesis condition. Eleven rabbits were included according to inclusion and exclusion criteria, and a total of twenty-two imaging data sets were analyzed for quantification. Results. In the basal study, total counts of the mixture decreased from 87,800.83 ± 12,622.76 to 42,733.14 ± 6,591.53 at 30 min and to 13,684.19 ± 1,774.90 at 60 min, and these decreases were statistically significant (p = 0.003). Emptying percentages were 51.39 ± 0.78% at 30 min and 84.32 ± 1.56 at 60 min and were statistically significant (p = 0.003). After intravascular atropine sulfate injection, total counts of the mixture decreased from 84,508.78 ± 11,871.48 to 64,995.18 ± 9,298 at 30 min and to 53,507.17 ± 7,258.98 at 60 min, and these decreases were statistically significant (p = 0.003). Emptying percentages were 23.10 ± 1.11% at 30 min and 36.63 ± 1.42 at 60 min and were statistically significant (p = 0.003). The difference between basal and post-atropine sulfate gastric emptying percentage at 30th (p = 0.003) and 60th (p = 0.003) min was statistically significant. Conclusion. The meal, used in this study, is non-nutrient, fatty-free, and semisolid and is easy to prepare and administer. Due to its semisolid nature, it offers a chance to evaluate the quantification of regional and total GE as well as the separate roles of the fundus and antrum.